An Automated Verification Process Based on Scan Technique - Alves, Gustavo R. (2000)
Matching the results achieved during circuit simulation with those extracted from circuit functioning is a common verification process. A large number of current verification techniques use the input / output vectors produced during functional simulation as the test vectors applied / compared against the circuit responses. Techniques that are more complete include extracting the values of internal sequential nodes and comparing these using internal scans. This paper describes a solution for verifying digital designs implemented in currently commercial available CPLDs. All internal flip-flops are included in a scan-chain accessible through the BST infrastructure (using a user-defined optional instruction), while the BS cells are used to apply the input test vectors and capture the circuit responses. These BS cells can either belong to the device-under-test or to other devices, the first controlled through the optional INTEST instruction and the second controlled through the mandatory EXTEST instruction. To speed up the verification process, the test program is automatically generated from information that encompasses the design & development phase.